PENJADWALAN DAN REKOMENDASI DOSEN PENGUJI SIDANG MUNAQASYAH BERBASIS CLOUD-AI INTEGRATED SYSTEM - Aidil Halim Lubis; Armansyah Armansyah; Ilka Zufria; Yusrizal Hakim; Dhafa Hibrizi Sitorus (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to create an information system for registering Munaqasyah or Colloquium hearings by combining Cloud computing and Artificial Intelligence (AI) technologies based on a decision support system. In this study, AI is used to select thesis research fields in order to recommend examiners who are suitable for the students' research topics and to schedule student munaqasyah hearings in a structured and automated manner. Cloud computing is useful for storing all examination requirements, minutes, etc. on a cloud platform that supports the process in real time. The system was developed using a phased Cloud-AI approach, namely planning, design, implementation, testing, and evaluation repeatedly. This system was created using a web platform and combines students' final assignments and lecturers' expertise as a basis for decision making. The research results show that this system can support more efficient examination registration and provide accurate recommendations for examiners and automatic scheduling. With the integration of Cloud-AI in this system, academic administration management can be more effective, and services for students and the management of munaqasyah examinations in the Computer Science study program can be improved. Keyword: Waterfall Development, Artificial Intelligence, Decision Support System, Munaqasyah Examination, Final Project.. Abstrak: Penelitian ini bertujuan membuat sistem informasi untuk pendaftaran sidang Munaqasyah atau Kolokium dengan menggabungkan teknologi Cloud computing dan Artificial Intelligence (AI) yang sederhana berdasarkan sistem pendukung keputusan. Pada penelitian ini, AI digunakan dengan cara memilih bidang penelitian skripsi agar bisa memberi rekomendasi dosen penguji yang sesuai dengan topik penelitian mahasiswa dan penjadwalan sidang munaqasyah mahasiswa secara terstruktur dan otomatis. Cloud computing berguna untuk penyimpanan semua dokumen syarat sidang, berita acara, dll pada platform cloud yang menunjang proses secara realtime. Pengembangan sistem dilakukan dengan pendekatan Cloud-AI yang bertahap, yaitu perencanaan, desain, implementasi, pengujian, dan evaluasi secara berulang. Sistem ini dibuat menggunakan platform web dan menggabungkan bidang tugas akhir mahasiswa serta keahlian dosen sebagai dasar untuk mengambil keputusan. Hasil penelitian menunjukkan bahwa sistem ini bisa mendukung pendaftaran sidang lebih efisien serta memberi rekomendasi dosen penguji yang tepat dan akurat dan penjadwalan secara otomatis. Dengan adanya integrasi Cloud-AI dalam sistem ini, maka pengelolaan administrasi akademik bisa lebih efektif, dan pelayanan bagi mahasiswa serta pengelolaan sidang munaqasyah di prodi Ilmu Komputer dapat meningkat. Kata kunci: Waterfall Development, Artificial Intelligence, Decision Support System, Sidang Munaqasyah, Tugas Akhir.